Mother’s Behavior in Searching for the Health Service of Malnourished Children in Lumut Sub-district, Tapanuli Tengah Regency of 2019 - Herida Purba; R. Kintoko Rochadi; Etti Sudaryati (Britain International of Exact Sciences (BIoEx) Journal, 2020)
This study deals with mother’s behavior in searching for the health service of malnourished children in Lumut Sub-district, Tapanuli Tengah Regency of 2019. Mother’s behavior in searching for the health services is a form of action taken to maintain the health of their children and to monitor the growth and development of children to grow healthily. The type of research is qualitative research. The study was conducted in several villages in the working area of Lumut Health Center, Lumut Sub-district, and Tapanuli Tengah Regency. The results showed that the lack of knowledge of children mothers due to low maternal education, so that mothers do not understand about malnutrition and the benefits of health care facilities. Low family income factors cause mothers to not provide proper and varied food for the family. Thus the mother only provides sufficient food that can last a long time such as salted fish and boiled fish.